Antiphase Boundaries as Faceted Metallic Wires in 2D Transition Metal Dichalcogenides. Issue 15 (8th June 2020) - Kim, Jung Hwa; Kim, Se‐Yang; Park, Sung O.; Jung, Gwan Yeong; Song, Seunguk; Sohn, Ahrum; Kim, Sang‐Woo; Kwak, Sang Kyu; Kwon, Soon‐Yong; Lee, Zonghoon
Abstract: Antiphase boundaries (APBs) in 2D transition metal dichalcogenides have attracted wide interest as 1D metallic wires embedded in a semiconducting matrix, which could be exploited in fully 2D‐integrated circuits. Here, the anisotropic morphologies of APBs (i.e., linear and saw‐toothed APBs) in the nanoscale are investigated. The experimental and computational results show that despite their anisotropic nanoscale morphologies, all APBs adopt a predominantly chalcogen‐oriented dense structure to maintain the energetically most stable atomic configuration. Moreover, the effect of the nanoscale morphology of an APB on electron transport from two‐probe field effect transistor measurements is investigated. A saw‐toothed APB has a considerably lower electron mobility than a linear APB, indicating that kinks between facets are the main factors of scattering. The observations contribute to the systematical understanding of the faceted APBs and its impact on electrical transport behavior and it could potentially extend the applications of 2D materials through defect engineering to achieve the desired properties. Abstract : Herein, the anisotropic nanoscale features of antiphase boundaries in 2H phase of transition metal dichalcogenides are investigated (i.e., saw‐toothed for transition metal‐facing and linear for chalcogen‐facing antiphase boundaries) in order to preserve the thermodynamically most stable atomic configurations. In addition, they have different in‐plane transport behavior because lots of kinks in the saw‐toothed antiphase boundary act as scattering centers.